Mortality and predictors of appropriate implantable cardioverter defibrillator therapy in Japanese patients with Multicenter Automatic Defibrillator Implantation Trial II criteria. Issue 1 (28th June 2016) - An, Yoshimori; Ando, Kenji; Soga, Yoshimitsu; Nomura, Akihiro; Nagashima, Michio; Hayashi, Kentaro; Makihara, Yu; Fukunaga, Masato; Hiroshima, Ken‐ichi; Nobuyoshi, Masakiyo; Goya, Masahiko
Abstract: Background: Data regarding long‐term mortality and factors influencing appropriate therapies in Japanese patients with implantable cardioverter defibrillators (ICD), who satisfy the Multicenter Automatic Defibrillator Implantation Trial II (MADIT II) criteria for primary prevention, remain scarce. Methods: A total of 118 consecutive patients who underwent ICD implantation without any prior ventricular arrhythmic event, from January 2000 to December 2012, were enrolled based on the MADIT II criteria: left ventricular ejection fraction (LVEF) of ≤30% with ischemic heart disease and at least 4 weeks after a myocardial infarction. We investigated the mortality and factors influencing appropriate ICD therapies in this population. Results: The mean age was 69±10 years, and the mean LVEF was 25.1±4.5%. During the median follow up of 1406 days, the mortality rate was 20%, and the incidence of appropriate ICD therapy was 37% at 3 years. Multivariate analysis by using Cox regression model showed that left ventricular diastolic diameter ≥60 mm (hazard ratio [HR], 2.31; 95% confidence interval [CI], 1.07–5.38; P =0.033) and the presence of non‐sustained ventricular tachycardia (NSVT) before implantation (HR, 2.26; 95% CI, 1.17–4.39; P =0.015) were independent predictors of appropriate ICD therapy. Conclusions: The mortality and incidence of appropriate ICD therapy were 20% and 37%, respectively, at 3 years in Japanese patients who met the MADIT II criteria during ICD implantation for primary prevention of sudden cardiac death. The presence of NSVT and dilated left ventricle independently predicted the incidence of appropriate ICD therapy after implantation.